RANCANG BANGUN SISTEM INFORMASI PENDAFTARAN DAN ABSENSI ASLAB BERBASIS CONTAINER-AS-A-SERVICE (CAAS) (STUDI KASUS: FASTAPI DAN GOOGLE CLOUD RUN) - rifa'i, Hikmal Dwi; Ali, Firman; Endaswari, Putri Mentari (Program Studi Informatika Fakultas Teknik Universitas Janabadra, 2026)
Manual management of laboratory assistants (aslab) often leads to problems such as inefficiency in data management, information delays, and a lack of transparency in the selection process. On the other hand, the development of information systems in campus environments is often hampered by traditional server infrastructure (IaaS) which is complicated to maintain and inefficient in terms of operational costs, especially during low traffic. This study aims to design and build an Aslab Registration, Administration, and Attendance Information System by implementing a modern architecture in the form of Container-as-a-Service (CaaS). The system is built using the Python FastAPI framework, packaged with Docker container technology, and deployed on Google Cloud Run services integrated with Google Cloud SQL. The research method uses a Research and Development (R&D) model adapted from the Borg & Gall model. The results of Black-Box testing and User Acceptance Testing (UAT) indicate that the system runs well in a serverless cloud environment and meets user functional needs. The use of a CaaS architecture provides significant advantages in terms of automatic scalability (auto-scaling), cost efficiency through a pay-per-request model, and ease of deployment compared to conventional server infrastructure.